Croatian Canadian Literature--Emigrant, Ethnic or Diasporic? - Šesnić, Jelena (2011)
In the context of several intersecting and distinct changes (globalization of cultural production, changes of immigration patterns, depoliticization of the study of Croatian diaspora) it becomes possible to introduce new interpretive models for more encompassing readings of literary production by Croats and their descendants in Croatian emigration communities world-wide. The focus of the essay is specifically on three case studies coming from Croatian Canadian literary corpus, namely, Katarina Pejaković, Ljerka Lukić, and Tony Fabijančić. Even though in their case the writing is split in terms of language (Croatian and English) and in terms of genre (poetry, non-fiction), it is argued that other indicators must be taken into account in order to capture the underlying similarity between these texts so as to enable us to reach some conclusions about the changing nature of literary production by and about Croats in different national contexts.
Projekt MZOS
Projekt MZOS
ENG